STUDI DESKRIPTIF KETERAMPILAN SOSIAL SISWA SMP NEGERI 5 LEMBANG - Hoyrl Kurniawan; Siti Fatimah; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Social skills are skills needed by every student. By having good social skills, students can also establish good relationships with the environment and peers. This study aims to describe the social skills of SMP Negeri 5 Lembang students who are in the adolescent phase, seen from the indicators of social skills of verbal responses, non-verbal responses and cognitive processes based on gender and class. The research method used in this research is descriptive quantitative. In this study, data were collected using a Likert scale social skills questionnaire based on the theory proposed by Michelson. The samples in this study were students of SMP Negeri 5 Lembang in grades VII, VII, and XI. The results showed that students' social skills based on verbal, non-verbal responses and cognitive processes seen from gender and class were in the moderate category, it was seen from verbal responses, positive or negative expressions and thoughts of students that could determine whether or not communication and interaction was good. What students do to their friends and their environment.   Keywords: : Descriptive Study, Student Social Skills, Adolescents